Basics of budgetary control - Aldibaeva, M. (Journal of Economic Research & Business Administration, 2016)
In this article features of budgetary planning within the interbudget relations are analysed and it is revealed that regardless of type of an economic system the problem resolution of financial equalization almost completely is competence of governing bodies of areas, and tasks enter a component a perspective of a budgetary and tax planning on different level. With regard to increasing the differentiation of local authorities in terms of income it should be noted that, firstly, as a rule, the greatest tax revenues per capita are concentrated in cities, where and supplies per the needs of the population is much higher due to more developed social and engineering infrastructure, the need to provide a wide range of public services compared to rural municipalities. Secondly, the subject has the ability to carry out the seizure and the subsequent redistribution of the tax revenues of the wealthiest municipalities in the funds of financial support to municipalities with low levels of socio-economic development.